Brazilian Consortium for the Study on Renal Diseases Associated With COVID-19: A Multicentric Effort to Understand SARS-CoV-2-Related Nephropathy - Teixeira Júnior, Antonio Augusto Lima; Neves, Precil Diego Miranda de Menezes; Lages, Joyce Santos; Cunha, Kaile de Araújo; Muniz, Monique Pereira Rêgo; Brito, Dyego José de Araújo; Watanabe, Andréia; Watanabe, Elieser Hitoshi; Onuchic, Luiz Fernando; Nunes, Lucas Lobato Acatauassu; Coutinho Filho, Antônio Fernando; Barcelos, Flávia Lara; et al. (Frontiers in Medicine, 2020)
Kidney involvement appears to be frequent in coronavirus disease 2019 (COVID-19). Despite this, information concerning renal involvement in COVID-19 is still scarce. Several mechanisms appear to be involved in the complex relationship between the virus and the kidney. Also, different morphological patterns have been described in the kidneys of patients with COVID-19. For some authors, however, this association may be just a coincidence. To investigate this issue, we propose assessing renal morphology associated with COVID-19 at the renal pathology reference center of federal university hospitals in Brazil. Data will come from a consortium involving 17 federal university hospitals belonging to Empresa Brasileira de Serviços Hospitalares (EBSERH) network, as well as some state hospitals and an autopsy center. All biopsies will be sent to the referral center for renal pathology of the EBSERH network. The data will include patients who had coronavirus disease, both alive and deceased, with or without pre-existing kidney disease. Kidney biopsies will be analyzed by light, fluorescence and electron microscopy. Furthermore, immunohistochemical (IHC) staining for various inflammatory cells (i.e. cells expressing CD3, CD20, CD4, CD8, CD138, CD68, and CD57) as well as angiotensin-converting enzyme 2 (ACE2) will be performed on paraffinized tissue sections. In addition to ultrastructural assays, in situ hybridization (ISH), IHC and reverse transcription-polymerase chain reaction (RT-PCR) will be used to detect Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) in renal tissue. For the patients diagnosed with Collapsing Glomerulopathy, peripheral blood will be collected for apolipoprotein L-1 (APOL1) genotyping. For patients with thrombotic microangiopathy, thrombospondin type 1 motif, member 13 (ADAMTS13), antiphospholipid and complement panel will be performed. The setting of this study is Brazil, which is second behind the United States in highest confirmed cases and deaths. With this complete approach, we hope to help define the spectrum and impact, whether immediate or long-term, of kidney injury caused by SARS-CoV-2.